PROCESSOS DENUDACIONAIS E A EVOLUÇÃO DO RELEVO NA REGIÃO DO ALTO ITAPECURU, ESTADO DO MARANHÃO - SANTOS, Helen Niedja Ferreira dos (2024)
This research aims to characterize the denudational processes and the evolution of the relief in the Alto Itapecuru region, in the state of Maranhão, by means of an integrated analysis of the lithology, the structural framework and the configuration of the relief and hydrography, using qualitative and quantitative techniques. The research involves a literature review, fieldwork, spatial analysis associated with the use of geoprocessing techniques, as well as laboratory and statistical analysis of sediment samples. The results showed that the contribution of the structural factor in the geomorphological configuration and evolution of the watercourses is reflected in the obedience of the river channels to the structural lineaments, which follow parallel patterns, within embedded valleys and aligned on faults and/or fractures. The application of morphometric indices yielded results that indicate neotectonic activity in this region. The RDE values showed 2nd order anomalies, especially near the headwaters of the rivers. This density of anomalies and the profiles with the greatest energetic strength are at altitudes between 407 m and 612 m, in terrain that concentrates the highest percentages of slopes and roughness, where sandstones of the Corda Formation predominate. The sediment analysis showed that fine sand is the main granulometric class transported by the river channels, which may be associated with the geological substrate of the study region, as it is part of the Parnaíba Sedimentary Basin, and this material is being deposited in the valleys, which are clogged with sediment, reflecting the low energy of the channels. In this region, the Alpercatas River has a transportation process and erosion potential that surpasses that of the Itapecuru River. The rocks of the Alto Itapecuru are weathered, porous and highly susceptible to erosion. These natural conditions indicate that the mechanical denudational processes are acting more vigorously and the evolutionary process is occurring naturally, as the sediments reflect this natural tendency.